2017
DOI: 10.1186/s13045-017-0493-0
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: MicroRNA-330-3p promotes cell invasion and metastasis in non-small cell lung cancer through GRIA3 by activating MAPK/ERK signaling pathway

Abstract: BackgroundBrain metastasis (BM) is associated with poor prognosis in patients with non-small cell lung cancer (NSCLC). Recent studies demonstrated that microRNA-330-3p (miR-330-3p) was involved in NSCLC brain metastasis (BM). However, the exact parts played by miR-330-3p in BM of NSCLC remain unknown. Discovery and development of biomarkers and elucidation of the mechanism underlying BM in NSCLC is critical for effective prophylactic interventions. Here, we evaluated the expression and biological effects of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 51 publications
3
54
0
Order By: Relevance
“…Pathway analysis of the total of 339 genes showed that altered genes are largely involved in cell division and cell cycle regulation (Table 1). For two hypermethylated genes in our analysis, ESX1, a homeodomain protein, was reported to regulate cell cycle progression and transcription [24-26], and GRIA3 has been shown to promote proliferation in nonneuronal cells [27, 28]. As other glutamate receptors, such as NMDA receptor, have an important function in podocyte biology and glomerular diseases, we selected GRIA3 for further analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pathway analysis of the total of 339 genes showed that altered genes are largely involved in cell division and cell cycle regulation (Table 1). For two hypermethylated genes in our analysis, ESX1, a homeodomain protein, was reported to regulate cell cycle progression and transcription [24-26], and GRIA3 has been shown to promote proliferation in nonneuronal cells [27, 28]. As other glutamate receptors, such as NMDA receptor, have an important function in podocyte biology and glomerular diseases, we selected GRIA3 for further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Kidney sections and isolated glomeruli were obtained from control (control-eNOS –/– ) and diabetic (STZ-eNOS –/– ) mice as described previously [27]. a Real-time PCR of Gria3 in isolated glomeruli is shown as a relative fold change to control mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that miR-330-3p can target the gene of program cell death 4 (PDCD4) to promote tumor [17]. MiR-330-3p is also related with metastasis and invasion of lung cancer, and glutamate receptor 3 (GRIA3) [18] and human manganese superoxide dismutase 2 (hSOD2) [19] are its two target genes. Researches found miR-330-3p is correlated with bad prognosis in breast cancer as well [20], in which miR-330-3p can target Collagen and Calcium Binding EGF Domains 1 (CCBE1) to promote cancer metastasis [21].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the MAPK pathway participates in regulating the invasion and metastasis of NSCLC; 26 thus, we explored the potential effects of OPN on the MAPK pathway. Western blotting showed that OPN overexpression increased p-MEK and p-ERK in A549 cells, and silencing of OPN had the opposite results ( Figure 3A and B).…”
Section: Opn Promotes a Malignant Phenotype Via The Mapk Pathwaymentioning
confidence: 99%